Level of appropriation of specific physical education competencies in secondary school students. - Rosario-Rodríguez, José Luis (Journal of Neonatal Surgery, 2025)
The ultimate goal of planning and implementing a Physical Education class is to achieve the comprehensive development of students. In this process, specific competencies must be developed that will contribute to the development of fundamental competencies. However, an assessment process must be established to verify the mastery of these competencies. The objective of this study was to determine the level of mastery of specific physical education competencies among secondary school students in the Dominican public education system. The methodology employed in this study was based on a quantitative, descriptive, and cross-sectional approach. The population consisted of 10,793 students. The sample was obtained in a stratified manner and totaled 1,196 students. The technique employed was a survey, and the instrument applied was a Likert-shaped questionnaire containing 42 questions. It was validated through expert judgment or the Delphi method and a factor analysis based on the KMO, obtaining an acceptable score of 0.841. The results showed that students maintained a positive level within the established scale for assessing specific physical education competencies. It was concluded that students had an average level of mastery of specific physical education competencies, which is significant in light of the secondary school graduation profile..